STUDI LITERATUR: PEMANFAATAN SUMBER BELAJAR LINGKUNGAN FISIK SEKOLAH UNTUK KETERAMPILAN MENULIS TEKS DESKRIPSI MURID SD - Faiz Satrio Yudhanto; Dian Indihadi (STKIP Subang, 2026)
Writing skills are seen as a difficult skill, this is based on the fact that the writing process requires the involvement of many skills at once, including reading, writing, thinking and reasoning about the object that will be the topic of the writing, based on this, this article will discuss and present the results of a literature study regarding the impact of the physical environment of schools on the descriptive text writing skills of elementary school students. The findings obtained from this review of research results indicate that the physical environment of schools presents great potential for pedagogical applications, especially as a resource to facilitate the teaching of descriptive texts in elementary education. The real school environment, including architectural structures, infrastructure provisions, botanical elements, and various phenomena that can be observed near students, plays an important role in providing a contextual, empirically verifiable, and meaningful learning environment. This direct experience engagement fosters a strong stimulus for students, encouraging sharp observation, sensory perception, and concrete information processing, thus empowering them to articulate their conceptualizations into clear and detailed descriptive text formats. Thus, the use of the school's physical environment as a learning resource in descriptive text learning is in line with the demands of the 2025 National Curriculum which emphasizes contextual learning, strengthening literacy, and developing students' productive language skills.